Stanley's Christmas adventure - Brown, Jeff, 1926-2003 (HarperTrophy, 2003)
When Santa quits his job a few days before Christmas because of too many greedy children, his daughter whisks young Stanley Lambchop and his family off to the North Pole to help change the old man's mind.